Spurious Amplification of a Plasmodium vivax Small-Subunit RNA Gene by Use of Primers Currently Used To Detect P. knowlesi - Imwong, M; Tanomsing, N; Pukrittayakamee, S; Day, N; White, N; Snounou, G (2009)
The PCR primers commonly used to detect Plasmodium knowlesi infections in humans were found to cross-react stochastically with P. vivax genomic DNA. A nested primer set that targets one of the P. knowlesi small-subunit rRNA genes was validated for specificity and for sensitivity of detection of <10 parasite genomes. Copyright © 2009, American Society for Microbiology. All Rights Reserved.